Student Accountability in Team-based Learning Classes. (January 2016) - Stein, Rachel E.; Colyer, Corey J.; Manning, Jason
Team-based learning (TBL) is a form of small-group learning that assumes stable teams promote accountability. Teamwork promotes communication among members; application exercises promote active learning. Students must prepare for each class; failure to do so harms their team's performance. Therefore, TBL promotes accountability. As part of the course grade, students assess the performance of their teammates. The evaluation forces students to rank their teammates and to provide rationale for the highest and lowest rankings. These evaluations provide rich data on small-group dynamics. In this paper, we analyze 211 student teammate assessments. We find evidence that teams consistently give the lowest evaluations to their least involved members, suggesting that the team component increases accountability, which can promote learning. From these findings we draw implications about small-group dynamics in general and the pedagogy of TBL in particular.